Cryoprecipitate indications and patterns of use in the pediatric intensive care unit: inappropriate transfusions and lack of standardization. Issue 8 (17th May 2016) - DeSimone, Robert A.; Nellis, Marianne E.; Goel, Ruchika; Haas, Thorsten; Vasovic, Ljiljana; Cushing, Melissa M.
Abstract : BACKGROUND: The dosage and indications for cryoprecipitate are not well studied for any patient population. Prior observational studies have suggested that 24% to 62% of cryoprecipitate transfusions are inappropriate, and there is limited information on patterns of cryoprecipitate use in children. The purpose of this retrospective study was to explore the indications and appropriateness of the use of cryoprecipitate in critically ill children. STUDY DESIGN AND METHODS: We retrospectively reviewed the electronic medical records for cryoprecipitate ordering and utilization in the pediatric intensive care unit at a large tertiary care center during a 4.5‐year period. RESULTS: For the 44 patients receiving cryoprecipitate, the only indication was for fibrinogen replacement and the most common clinical scenarios were recent cardiac surgery (39%) and disseminated intravascular coagulation in the setting of sepsis (32%). Cryoprecipitate was often transfused empirically at higher‐than‐recommended doses without a known pretransfusion fibrinogen level, and the majority (61%) of cryoprecipitate transfusions were deemed inappropriate according to our institutional guidelines. The indications selected for cryoprecipitate by providers during physician order entry matched the clinical scenario, assessed by chart and laboratory data review, in only 18% of patients. There was no significant difference in red blood cell usage in the 6‐hour windows before and after cryoprecipitate transfusion. CONCLUSION: Our study demonstrates a lack of standardization for the use of cryoprecipitate in critically ill children, including many inappropriate transfusions at higher‐than‐recommended dosing. Prospective randomized clinical trials are warranted to help determine appropriate indications and efficacious cryoprecipitate dosing in the pediatric population.